(untitled) (Jurnal Peternakan Lingkungan Tropis, 2021)
The phenotype of livestock can describe the quality of livestock which will affect the selling value of the livestock in the market. The purpose of this study was to determine the effect of phenotypic characteristics on the selling price of Indonesian local goats in the city of Samarinda. The study used male goats aged 1 to 2 years. The number of samples in this study were 114 male goats and 16 respondents. The method used in this research is multiple linear regression analysis and correlation analysis. The breeds of goats traded in the city of Samarinda are Jawarandu goats, Etawah hybrids and Kacang goats. The results of multiple linear regression analysis of the variables that have a significant effect on the selling price, namely the length of the horn with a significance of 0.006 > 0.05 have a significant effect on the selling price. Based on the correlation analysis, the degree of relationship between the inner R value of the Jawarandu goat, which is 0.665, means that chest circumference, body length, gumba height and horn length have a strong correlation to the selling price. Etawah crossbreed goats have a correlation R of 0.806 in the sense that it has a very strong correlation to the selling price. Peanut goat has a very strong correlation to the selling price with an R value of 1,000.